Trust relationships in schools: supporting or subverting implementation of school-wide initiatives - Gregory, Jess L. (School Leadership & Management, 2017)
This article explores trust relationships in schools that involve disparities in power. Trust is a key factor in developing a positive school culture and strong leadership in schools. Even with the flattening of hierarchies through more distributive models of leadership, disparities in power exist and they influence the trust relationships in schools. Through both French and Raven’s and Follett’s conceptualisations of power, five brief autobiographical stories about trust in schools are deconstructed. Lessons for leadership are gleaned from the power relationships in the autobiographical stories of trust shared by public school educators. In addition, general recommendations are offered that are relevant for all levels of school leadership including but not limited to the instructional coach, the curriculum supervisor, the building principal, and the classroom teacher.
8 citations (Crossref) [2023-10-31]
Keywords: Follett; French & Raven; Trust; change leadership; dept.edl; educational leadership; power